2022
DOI: 10.3389/fimmu.2022.942446
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of four immune-related signatures in keloid

Abstract: A keloid is a fibroproliferative disorder of unknown etiopathogenesis that requires ill-defined treatment. Existing evidence indicates that the immune system plays an important role in the occurrence and development of keloid. However, there is still a lack of research on the immune-related signatures of keloid. Here we identified immune-related signatures in keloid and explored their pathological mechanisms. Transcriptomic datasets (GSE7890, GSE92566, and GSE44270) of keloid and normal skin tissues were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 107 publications
0
5
0
Order By: Relevance
“…In current study, we pay our attention to human unique skin fibrotic disease-keloids, though lacking relevant animal models, and therefore difficult to study in terms of etiology and pathogenic mechanisms. While some genetic and environmental factors associated with keloid formation are identified (5,(7)(8)(9)(10)(11)(12), none of them can be considered as a main explanation. It is highly probable that the formation of keloids is indeed a resultant of multiple factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In current study, we pay our attention to human unique skin fibrotic disease-keloids, though lacking relevant animal models, and therefore difficult to study in terms of etiology and pathogenic mechanisms. While some genetic and environmental factors associated with keloid formation are identified (5,(7)(8)(9)(10)(11)(12), none of them can be considered as a main explanation. It is highly probable that the formation of keloids is indeed a resultant of multiple factors.…”
Section: Discussionmentioning
confidence: 99%
“…The initiation and support of this fibroblastic pathology remains elusive. Previous research indicates that keloids are related to genetic features (5,6), mechanical properties of the skin (7), nutrition and metabolism (8), composition of local hematopoietic compartment (9)(10)(11), and neuro-endocrine interactions (12).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have reported that keloid broblasts can promote or inhibit keloid development through immune processes such as stress induced by immune cells in the microenvironment. In the analysis of keloid tissues, it was found that the number of macrophages, T cells, mast cells and Langerhans cells in keloid was signi cantly increased, and these immune cells could secrete cytokines to stimulate collagen production and promote scar process (Wilgus et al, 2020;Wang et al, 2022;Lv et al, 2020). Some researchers have also found that macrophages, Treg cells, CD 8+ T cells, dendritic cells and natural killer cells play an important role in the pathological process of keloid when analyzing keloid immune in ltration (Niessen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It is mainly characterized by the infiltration of inflammatory cells such as macrophages, lymphocytes, mast cells and neutrophils (3). Inflammatory mediators secreted by immune cells induce fibroblasts (FBs) fibrosis and keratinocytes (KCs) re-epithelialization, resulting in excessive deposition of a large amount of extracellular matrix (ECM) components, which is accompanied by mechanical stretching and angiogenesis and eventually develops into PS (4)(5)(6). Furthermore, recent studies have shown that oxidative stress and epigenetic regulation are involved in the occurrence of PS (7,8).…”
Section: Introductionmentioning
confidence: 99%